PEMANFAATAN TEKHNOLOGI PEMBELAJARAN BERBASIS APLIKASI KINE MASTER UNTUK PENGUATAN NILAI-NILAI ISLAM KEPADA PESERTA DIDIK - Jasiah; Majidi, M.Wahid; Pastilah, Lijar; Hakim, M.Luqman; Pratama Putra, Aulia (Jurnal Biogenerasi, 2025)
This research discusses the utilization of technology, specifically the KineMaster application, in Islamic Education (PAI) learning to strengthen Islamic values among students. In the digital era, the use of educational technology is increasingly important to create an interactive and engaging learning environment. This study employs a qualitative approach by collecting data from various related literature. The findings indicate that the KineMaster application can enhance learning effectiveness through creative material delivery, such as educational videos that visualize complex religious concepts. Furthermore, technology provides broader access to Islamic learning resources, strengthens student engagement, and facilitates interactive discussions. The readiness of educators and students to adapt to technology is key to the successful implementation of this learning method.